Effect of Drying Methods on Fatty Acid Profile of Hazelnut (Corylus avellana L.): A Review - Ali Turan (Turkish Journal of Agriculture: Food Science and Technology)
Hazelnut is the important agricultural product of the Eastern and Western Black Sea region of Turkey and is usually exported to the world market dried and unshelled. Hazelnut in husks are dried generally grass and concrete ground under the sun. The traditional sun-dried process (concrete and grass ground) used by hazelnut farmers takes about 10 to 25 days counting on the weather conditions. If rainfall is high during the harvesting period, drying takes longer and causes the harvest and spoilt. Rapid postharvest processing, mostly in husking and drying, is crucial for the quality the last product, among which the hazelnut drying plays essential role. Because sun-dried on the concrete and grass ground increase fungal activities of hazelnuts and the risk of mycotoxin development due to mould growth. And also, under the action light and heat lipid molecules are released free fatty acids, which can affect the stability of oil. Dryer can prevent mould growth and oil oxidation. Thus, drying machine appears to be a promising strategy for hazelnut drying.